Compensatory role of the NBCn1 sodium/bicarbonate cotransporter on Ca2+-induced mitochondrial swelling in hypertrophic hearts - Vargas, Lorena Alejandra (2017)
NBC Na+/HCO3 − cotransporter (NBCn1) and NHE1 Na+/H+ exchanger have been associated with cardiac disorders and recently located in coronary endothelial cells (CEC) and cardiomyocytes mitochondria, respectively. Mitochondrial NHE1 blockade delays permeability transition pore (MPTP) opening and reduces superoxide levels, two critical events exacerbated in cells of diseased hearts. Conversely, activation of NBCn1 prevented apoptosis in CEC subjected to ischemic stress. We characterized the role of the NHE1 and NBCn1 transporters in heart mitochondria from hypertrophic (SHR) and control (Wistar) rats. Expression of NHE1 was analyzed in left ventricular mitochondrial lysates (LVML), by immunoblots. NHE1 expression increased by ~40% in SHR compared to control (P < 0.05, n = 4). To examine NHE1-mediated Na+/H+ exchange activity in cardiac hypertrophy, mitochondria were loaded with BCECF-AM dye and the maximal rate of pHm change measured after the addition of 50 mM NaCl. SHR mitochondria had greater changes in pHm compared to Wistar, 0.10 ± 0.01 vs. 0.06 ± 0.01, respectively (P < 0.05, n = 5). In addition, mitochondrial suspensions from SHR and control myocardium were exposed to 200 μM CaCl2 to induce MPTP opening (light-scattering decrease, LSD) and swelling. Surprisingly, SHR rats showed smaller LSD and a reduction in mitochondrial swelling, 67 ± 10% (n = 15), compared to control, 100 ± 8% (n = 13). NBC inhibition with S0859 (1 μM) significantly increased swelling in both control 139 ± 10% (n = 8) and SHR 115 ± 10% (n = 4). Finally, NBCn1 Na+/HCO3 − cotransporter increased by twofold its expression in SHR LVML, compared to normal (P < 0.05, n = 5). We conclude that increased NBCn1 activity may play a compensatory role in hypertrophic hearts, protecting mitochondria from Ca<sup2+-induced MPTP opening and swelling.